The role of spiritual corporate culture in improving company performance - Mahfud, Imam; Ulpah, Mariya; Sholichah, Inti Ulfi (Journal of Economics and Business Letters, 2024)
This study discusses the role of a spiritual corporate culture in improving company performance. This study aimed to determine the role of spiritual corporate culture in improving company performance. This research uses a library research method with descriptive analysis. The research data collection technique was obtained from books, various journals, and various other articles, and then an analysis was carried out to obtain research results. The results of the study showed that the results of aqidah or tauhid motivation manifested in Faith in Allah SWT, Faith in the Holy Book of the Qur'an, and Faith in the Apostles had a significant influence on religious performance. Several studies have found research results that show that there is a significant relationship between spiritual culture and company performance, Islamic culture has a significant influence on employee performance, which ultimately will improve company performance. The industrial sector in this country shows good growth, but on the other hand, there are still several strategic problems that hinder business growth, namely the quality and quantity of human resources that are not optimal. Human resources are a central factor in a company, and human resources that can compete really help companies achieve their goals and produce good performance. Human resources are an important part of a company, especially in achieving common goals.